2003
DOI: 10.1038/nri1030
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation in the tissues by γδ T cells

Abstract: For a T-cell subset to be classified as immunoregulatory, it might reasonably be predicted that in its absence, animals would experience pathological immune dysregulation. Moreover, reconstitution of the subset should restore normal immune regulation. So far, these criteria have been satisfied by only a few of the candidate regulatory T-cell subsets, but among them is the intraepithelial gammadelta T-cell receptor (TCR)+ subset of mouse skin. In this article, we look at immunoregulatory gammadelta T cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
285
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(298 citation statements)
references
References 96 publications
8
285
1
4
Order By: Relevance
“…However, most of the studies on the roles of ␥␦ T cells in the epithelium rather revealed their immunoregulatory properties (36,37). In this study, we clearly demonstrated an involvement of resident ␥␦ T cells at the very early stage of host defense against bacterial infection through IL-17 production.…”
Section: Discussionmentioning
confidence: 52%
“…However, most of the studies on the roles of ␥␦ T cells in the epithelium rather revealed their immunoregulatory properties (36,37). In this study, we clearly demonstrated an involvement of resident ␥␦ T cells at the very early stage of host defense against bacterial infection through IL-17 production.…”
Section: Discussionmentioning
confidence: 52%
“…Treg suppress cd cell cytotoxicity and cytokine production gd T cells are well known for their cytotoxic function in both mice [4] and humans [2], which constitutes a strong basis for gd-T-cell-based cancer immunotherapies [2]. We tested whether this activity could be directly inhibited by Treg in 3-day co-cultures.…”
Section: Resultsmentioning
confidence: 99%
“…gd T cells are innate-like lymphocytes known to mount robust responses to infectious pathogens [1] and tumors [2], while also regulating tissue homeostasis and repair [3]. Importantly, several of these functions are non-redundant, as demonstrated by the immunopathology phenotypes of TCR-d-deficient mice [4]. It is also well documented that upon pathogen challenge (for example, with Plasmodium falciparum, Mycobacterium tuberculosis, Haemophilus influenzae, or Streptococcus pneumoniae), gd T cells are one of the immune populations that expands most dramatically in human peripheral blood [1,5,6].…”
mentioning
confidence: 99%
“…Circulating gd T cells show a more diverse TCR repertoire, but make up only 0.5-3% of all T cells in the blood and in secondary lymphoid organs such as lymph nodes and spleen. Both mucosal and circulating gd T cells seem to play specific roles in the regulation and execution of host responses to many pathogens [1][2][3].Recently, gd T cells have received an increasing attention as main producers of the pro-inflammatory cytokine IL17A [4][5][6][7]. In contrast to the progress made in understanding their counterparts of the ab T-cell lineage, the biological role of gd T cells is only slowly emerging.…”
mentioning
confidence: 99%
“…Circulating gd T cells show a more diverse TCR repertoire, but make up only 0.5-3% of all T cells in the blood and in secondary lymphoid organs such as lymph nodes and spleen. Both mucosal and circulating gd T cells seem to play specific roles in the regulation and execution of host responses to many pathogens [1][2][3].…”
mentioning
confidence: 99%